Teknologi Smart Supply Chain (SSC) Pada Kinerja Hijau Yang Dimediasi Oleh Green Operations, Green Relationship Dan Customer Green Information Sharing - Ismail Ismail; Kurniawati Kurniawati; Yolanda Masnita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the roleresearchers want to know how the influence of Smart Supply chain (SSC) Technologies on Green Performance Mediated by Green Operations, green relationships and customer green information sharing, research using a questionnaire method of 222 respondents who work in manufacturing companies that implement Smart Supply chain (SSC) Technologies,The results of the study found that implementationSmart Supply chain (SSC) Technologies is able to improve the performance of Green Performance, Green Operations, green relationships and customer green information sharing. Green performance is also influenced by green relationships and customer green information sharing, while green operations cannot affect green performance. directly, it was found that green relationships and customer green information sharing were able to mediate the effect of Smart Supply chain (SSC) Technologies on green performance while green operations had not been able to mediate the relationship between Smart Supply chain (SSC) Technologies and green performance, this study found the importance of implementing Smart Supply chain (SSC) Technologies in the digital industry and distribution channels are not only physical supply chains but digital supply chains through the variable customer green information sharing used in this study